2016
DOI: 10.1038/srep38304
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrary Inequality in Reputation Systems

Abstract: Trust is an essential condition for exchange. Large societies must substitute the trust traditionally provided through kinship and sanctions in small groups to make exchange possible. The rise of internet-supported reputation systems has been celebrated for providing trust at a global scale, enabling the massive volumes of transactions between distant strangers that are characteristic of modern human societies. Here we problematize an overlooked side-effect of reputation systems: Equally trustworthy individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 42 publications
3
58
0
1
Order By: Relevance
“…Without a reputation system, interacting with newcomers generates private information about the trustworthiness of these newcomers that may be worthwhile in the longer run, but in the presence of a reputation system, this information is no longer private and actors instead have an incentive to free-ride on others generating this information, which in theory makes establishing a good reputation harder for newcomers. Third, reputation systems may generate arbitrary inequality through "reputation cascades" (Frey and van de Rijt 2016). Because actors prefer to cooperate with partners who already have established a reputation of trustworthiness, interaction may concentrate on just a few actors who then receive a disproportional share of the benefits from exchange, to the expense of others who might be equally trustworthy.…”
Section: Solutions For Two-person Dilemmasmentioning
confidence: 99%
“…Without a reputation system, interacting with newcomers generates private information about the trustworthiness of these newcomers that may be worthwhile in the longer run, but in the presence of a reputation system, this information is no longer private and actors instead have an incentive to free-ride on others generating this information, which in theory makes establishing a good reputation harder for newcomers. Third, reputation systems may generate arbitrary inequality through "reputation cascades" (Frey and van de Rijt 2016). Because actors prefer to cooperate with partners who already have established a reputation of trustworthiness, interaction may concentrate on just a few actors who then receive a disproportional share of the benefits from exchange, to the expense of others who might be equally trustworthy.…”
Section: Solutions For Two-person Dilemmasmentioning
confidence: 99%
“…However, earlier research on reputation systems (in both online and offline contexts) has shown that such systems have a tendency to create winner-takes-all dynamics, in which differences in candidates' reputations become disconnected from objective differences in ability and quality [19,25,41]. Indeed, emerging evidence suggests that many of the existing freelancing platforms are extremely unequal in terms of employees' earnings [56].…”
Section: Introductionmentioning
confidence: 99%
“…A major benefit of networks is that they greatly protect members against opportunism and exchange hazards than market transactions (e.g., Bowles & Gintis, 2004;Erikson & Samila, 2015;Granovetter, 2017;Jackson, Rogers, & Zenou, 2017;Kollock, 1994;Raub, Buskens, & Frey, 2013). At the same time, large-scale market interactions increase the possibilities of benefiting from economies of scale, specialisation and gains from trade (e.g., Algan & Cahuc, 2010;Bulte, Kontoleon, List, Turley, & Voors, 2017;Dixit, 2004;Frey & Van de Rijt, 2016;Greif, 2006;Smith, 2017Smith, [1776).…”
Section: Introductionmentioning
confidence: 99%